Analisis Penerimaan Pengguna Terhadap Aplikasi Pencari Makanan Non Halal di Kota Batam Menggunakan Metode TAM - Li Cen; Willsen Austin; Tony Wibowo (Komputa : Jurnal Ilmiah Komputer dan Informatika, 2026)
In Batam City, despite its varied demographic makeup, the non-Muslim population encounters difficulties in finding verified non-halal food options due to scattered information. This study's main objective is to assess user acceptance of a non-halal food finder app using the Technology Acceptance Model (TAM) as its theoretical basis. The research examines the impact of Perceived Ease of Use and Perceived Usefulness on users' behavioral intentions and actual usage in Batam. A quantitative method was utilized, involving 400 non-Muslim participants chosen through Simple Random Sampling, with data analyzed using SPSS. The statistical findings reveal that all five hypotheses are significantly validated. Importantly, Perceived Ease of Use greatly influences Perceived Usefulness, and together, these factors enhance a positive Attitude Toward Using, which significantly boosts Behavioral Intention and Actual Usage. The study offers a dual contribution: theoretically, it broadens TAM applications to services aimed at minorities; practically, it provides a strategic solution to close information gaps for the non-Muslim community. Therefore, the study concludes that the application is highly pertinent and widely accepted.